Atopic dermatitis in the elderly. (2nd January 2020) - Williamson, S.; Merritt, J.; De Benedetto, A.
Summary: Atopic dermatitis (AD, also known as atopic eczema) is a chronic and relapsing skin disease, affecting over 230 million people worldwide. It commonly is seen in patients who have other allergic conditions including asthma and allergic rhinitis (hay fever) and is recognised by an itchy rash and dry irritated skin. The majority of patients first develop AD at a young age, however it can occur later in life as well. With a growing elderly population and expectations for a good quality of life, the impact of AD in the elderly deserves some attention. Many elderly patients present with itching and dry skin to dermatology, allergy, and primary care clinics, and there is a lack of information available to clinicians regarding the proper diagnosis and management of these patients. Indeed, most investigations and clinical care guidelines about AD do not include patients aged 60 years and older as a separate group from younger adults. This review article, from the United States, aimed to present an overview of changes in the body that naturally occur with aging, that may cause elderly patients to be susceptible to developing AD. Interestingly, many age‐related changes overlap with key characteristics of AD, such as reduced skin barrier function, impaired inflammation, and increased bacterial (especially Staphylococcal ) infections. This work aims to provide a better understanding of the aging‐related pathophysiology (workings within the body) of AD and identify gaps in knowledge, thus opening new areas of research for future investigation. This summary relates to the study: Atopic dermatitis in the elderly: a review of clinical and pathophysiological hallmarks Abstract : Linked Article: Williamson et al. Br J Dermatol 2020; 182 :47–54